Land`s end: Capitalist relations on an indigenous frontier - Li, Tania Murray (Durham Duke University Press, 2014)
rawing on two decades of ethnographic research in Sulawesi, Indonesia, Tania Murray Li offers an intimate account of the emergence of capitalist relations among indigenous highlanders who privatized their common land to plant a boom crop, cacao. Spurred by the hope of ending their poverty and isolation, some prospered, while others lost their land and struggled to sustain their families.